Ethical Foundations for Strengthening Professional Conduct in Modern Policing Practices - Susilo Teguh Raharjo (Universitas Negeri Semarang, 2025)
Ethics plays a central role in shaping professional conduct and public trust in modern policing. As societal expectations evolve, police organizations face increasing pressure to behave transparently, uphold human rights, and maintain accountability. This study examines the ethical dimensions of policing through an analysis of decision-making models, institutional frameworks, and professional standards that influence officer behavior. Using a mixed-methods design, data were gathered from 62 semi-structured interviews with officers, community leaders, and legal experts, as well as document reviews of internal codes of conduct and oversight reports. Findings indicate that ethical awareness training reduces complaint rates by 27% and enhances officers’ ability to exercise discretion proportionately during high-stakes encounters. Nevertheless, organizational culture, peer influence, and inconsistent disciplinary mechanisms remain significant barriers to ethical compliance. The study concludes that ethics must be embedded in recruitment, training, leadership, and accountability systems to build a resilient and trustworthy police institution. The research contributes to policing science by offering a structured ethical framework that integrates normative principles with operational realities.